The important role of apolipoprotein A-II in ezetimibe driven reduction of high cholesterol diet-induced atherosclerosis. (January 2019) - Yan, Yi; He, Fei; Li, Zhonghao; Xu, Ruoting; Li, Ting; Su, Jinyu; Liu, Xianyan; Zhao, Ming; Wu, Wei
Abstract: Background and aims: It has been well established that ezetimibe blocks cholesterol absorption to prevent the negative effects of a high-fat diet in atherosclerosis. However, the exact mechanism is unknown. Here we use a transgenic zebrafish, which expresses different fluorescent proteins on either endothelial cells or granulocytes and macrophages, to explore the specific mechanism of ezetimibe and its role in reducing atherosclerosis-related hypercholesteremia. Methods: Zebrafish larvae were exposed to a control diet, high cholesterol diet (HCD) or a HCD with ezetimibe treatment. Both the control diet and high cholesterol diet were mixed with red or green fluorophore labeled cholesteryl ester to trace lipid distribution. Isobaric tags were used for relative and absolute quantification to examine protein expression profiles of zebrafish larvae in the different treatment groups. To knock down Apo A-II and investigate the role of Apo A-II in the anti-atherosclerotic function of ezetimibe, we used morpholinos to target zebrafish Apoa2 mRNA. To confirm ezetimibe regulatory role on Apo A-II expression, siRNA against HNF4, PPARα, and SREBP1 were transfected into HepG2 cells. Results: The results show that ezetimibe increased the expression of Apo A-II but failed to reduce vascular lipid accumulation and macrophage recruitment induced by the HCD diet when Apo A-II was knocked down. Finally, we found that ezetimibe increased the expression of Apo A-II through HNF4 and PPARα transcriptional factors. Conclusions: Our data indicates that ezetimibe may not only prevents atherosclerosis by inhibiting cholesterol absorption in the intestine, but also by increasing the expression of Apo A-II in hepatocytes, thereby enhancing reverse cholesterol transport and removing excess cholesterol from the periphery. Graphical abstract: Highlights: Ezetimibe alleviates high cholesterol diet-induced zebrafish pro-atherosclerotic lesions by increasing Apo A-II expression. Ezetimibe increases Apo A-II expression through HNF4 and PPARα transcriptional factors in HepG2 cells. Increased Apo A-II is beneficial to the recovery of macrophages cholesterol efflux, which could reduce the risk of atherosclerosis.